ON D-PENCIL SURFACE BY USING DARBOUX FRAME IN MINKOWSKI 3-SPACE - Sariaydin, Muhammed T.; Körpınar, Talat (EDITURA BIBLIOTHECA-BIBLIOTHECA PUBL HOUSE, 2019)
In this paper, the D - Pencil surface is studied in Minkowski 3-space. By using Darboux Frame in Minkowski space, we give the necessary and sufficient condition for a pencil surface. Then, we obtain general conditions of each other different G(1), G(2), G(3) developable ruled surface with the line of curvature of the pencil surface. Finally, we construct the corresponding surfaces which possessing some representative curves as lines of curvature.
Keywords: The line of curvature; Darboux frame; Pencil Surface